Controversies in the Workup and Surgical Management of Parotid Neoplasms. (23rd June 2020) - Moore, Michael G.; Yueh, Bevan; Lin, Derrick T.; Bradford, Carol R.; Smith, Richard V.; Khariwala, Samir S.
Abstract : Objective: Parotid neoplasms are a rare heterogeneous group of tumors with varied clinical presentation and behavior. Here we provide an evidence‐based review of the contemporary approach to evaluation and surgical management of parotid tumors. Data Source: PubMed and Web of Science Databases. Review Methods: Searches of the PubMed and Web of Science databases were performed on subjects related to the diagnosis and surgical management of parotid neoplasms. Particular emphasis was placed on the following areas: evaluation of parotid tumors, including imaging workup and the utility of fine‐needle aspiration; extent of surgery of the primary lesion, including the extent of parotidectomy as well as oncologic management of the facial nerve; the extent of surgery of involved and at‐risk cervical lymphatics; and parotid bed reconstruction. Articles published from 2014 to the present were prioritized, supplementing with information from prior studies in areas where data are lacking. Conclusion: A summary of the literature in these areas is outlined to provide an evidence‐based approach to evaluation and management of parotid neoplasms. Implications for Practice: While data are available to help guide many aspects of workup and management of parotid neoplasms, further research is needed to refine protocols for this heterogeneous group of diseases.